The choice of external financing source: The role of company size and stock liquidity - Streńczak, Szymon; Kubiak, Jarosław (Economics and Business Review, 2023)
This paper aims to answer whether firms of different sizes and stock liquidities differ in the choice of external sources of financing in companies listed in CEE countries. To this end the net debt issuance is regressed on the financial deficit. In regressions Pecking Order Coefficients are allowed to vary across firms with different sizes and stock liquidities. The results indicate that companies with less liquid shares prefer issuing debt to cover financial deficits more than companies with more liquid shares. This implies that stock liquidity may substitute debt issuance in alleviating the adverse effects of information asymmetry, especially in relatively small companies. This is the first study in which the relationship between liquidity and debt-equity choice is considered solely from a pecking order theory point of view. Also this is the first study in which stock liquidity effects on capital structure are studied in the CEE countries. Research results may point to the advantages of increasing the liquidity of shares which may contribute to reducing information asymmetry and thus a better allocation of resources.